Evaluation Criteria On Ambience-Based True Random Number Generators - Abu, Nur Azman; Abdul Latip, Shekh Faisal; Sahib @ Sahibuddin, Shahrin (Malaysian Society for Cryptology Research, 2018)
There is a need nowadays to ensure information security which is independent of the security mechanism of physical medium. Cryptography still remains an important science in daily life, be it for sovereignty use or the privacy of individuals. Ultimately, the security of the interoperating open cryptosystem must reside only in the key being used. It must be true random key. It is a challenging task to generate a true random key live on demand suitable for cryptographic applications. This paper shall formally propose an evaluation criteria on a true random number generator (TRNG). An evaluation has been done on various TRNG for cryptographic keys. This paper will also classify recent TRNGs into several groups. A new true random generator has been developed based on the air ambience for cryptographic application and evaluated against other TRNGs under the proposed evaluation criteria.